Charging and Discharging Control of Li-Ion Battery Energy Management for Electric Vehicle Application - Verasamy, M.; Faisal, M.; Ker, Pin Jern; Hannan, M A (International Journal of Engineering and Technology, 2018)
Electric vehicle (EV) is now replacing the conventional fuel driven vehicle as it has strong contribution to face the challenges of global warming issues. This system has the energy storage device which can be introduced by lithium-ion (li-ion) battery banks. Lithium-ion is mostly popular because of its high capacity and efficiency. Nevertheless, li-ion battery needs protective mechanism to control overcharged or undercharged of the cell that can reduce the life expectancy and efficiency.Â Hence, a control model needs to develop to enhance the protection of battery. Therefore, the key issue of the research is to investigate the performance of Li-ion battery energy management system (BMS) for electrical vehicle applications by monitoring and balancing the cell voltage level of battery banks using Simulink software. A bidirectional flyback DC-DC converter is investigated in the BMS model to control the undercharging or overcharging of cells. An intelligent charge control algorithm is used for this purpose. Backtracking search optimization algorithm (BSA) is implemented to optimize the parameters for generating regulated PWM signal. Obtained results were observed within the safety operating range of Li-ion battery (3.73 V â€“ 3.87V).